JEJAK KESINAMBUNGAN MADRASAH DINIYAH MUAWANATUL MUSLIMIN SEJAK 1915 HINGGA 2012 DI KUDUS: STUDI SEJARAH - Moh Rosyid (INFERENSI: Jurnal Penelitian Sosial Keagamaan, 2012)
This research focuses on the existence of a non formal Islamic educational institution - Muawanatul Muslimin – run by the community in Kudus Regency, Central Java since 1915. Characteristics of the school are: founded and managed by the kyai; specific subjects; distinctive dress patterns; learning time adjusted to the conditions of students; qualified to continue formal higher education; male students only; flexible financial management; respect for educators; holiday on Friday; and simple learning tool. Constraints faced by madrasa are: afternoon learning time; government policies; no diploma certificates qualified for the formal employment; the proliferation of the number of madrasa diniyah in Kudus; extracurricular and additional hours in formal educational institutions. The last two were prioritized by students in formal educational institutions.